Minimally invasive mitral valve surgery after previous sternotomy: A propensity‐matched analysis. Issue 9 (6th June 2021) - Hamandi, Mohanad; Squiers, John J.; Lanfear, Allison T.; Banwait, Jasjit K.; Meidan, Talia G.; Smith, Robert L.; Hutcheson, Kelley; DiMaio, John Michael; Mack, Michael J.; George, Timothy J.; Ryan, William H.
Abstract: Background: Although the incidence of mitral valve (MV) surgery after previous open‐heart surgery is increasing, there is no consensus regarding the optimal surgical approach. Reoperative MV surgery is most commonly performed via sternotomy (ST). We sought to determine whether minimally‐invasive (MIS) reoperative MV surgery is safe and feasible. Methods: All patients with a history of ST undergoing MV surgery with or without concomitant tricuspid or atrial fibrillation surgery at a single institution from 2007 to 2018 were retrospectively reviewed. ST and MIS approaches were compared using propensity‐matched analysis. The coprimary endpoints were operative mortality and 1‐year survival, and secondary endpoints were operative complications and length of stay. Results: A total of 305 isolated MV reoperations were performed: 199 (65%) MIS and 106 (35%) ST. MIS patients were older than ST patients (71 [63, 76.5] vs. 66 [56, 72] years, p < .01), more likely to have undergone prior coronary artery bypass grafting (57% vs. 27%, p < .01), and less likely to have had prior valve surgery (55% vs. 78%, p < .01). In unmatched comparisons, operative mortality was significantly lower among MIS patients (3.0% vs. 8.5%, p = .04), but 1‐year mortality was similar (14.4% vs. 15.6%, p = .8). After propensity matching, 88 pairs had excellent balance across baseline characteristics. Mortality was similar among MIS and ST patients at 30 days (3.4% vs. 8%, p = .19) and 1 year (15.9% vs. 16.5%, p = .9). RBC and fresh frozen plasma transfusions were significantly lower in the MIS group ( p < .01). Conclusions: A minimally invasive approach is a safe alternative in patients with prior ST undergoing MV surgery.